ANALISIS KINERJA KEUANGAN PADA KOPERASI BMT SYARIAH KECAMATAN BANGILAN KABUPATEN TUBAN - sufianti, ima; Rahayu, Susilowati; Novaliya, Novaliya; Lestariatun, Lestariatun (GEMA EKONOMI, 2018)
The performance of company's keunagan is a description of thefinancial condition of a company that is analyzed with the tools offinancial analysis, so it can be known about either the poor financialcondition of a company that reflects the performance of work in a certainperiod. A good financial performance can be judged from the results of ananalysis that gets a percentage in accordance with predeterminedstandards. The guidelines used in measuring the financial performance ofthis cooperative using the standard decision of the State Minister ofCooperatives and Small and Medium Enterprises of the Republic ofIndonesia No. 96 / kep / M.KUKM / IX / 2004 on Standard OperationalGuidelines for Cooperative Savings and Loans Management andCooperative Savings and Loan Units. The location of this research islocated in BMT Syariah District Bangilan Tuban Regency. The analystmethod used is descriptive method.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475680